Pengaruh Penerapan Model Problem Based Learning Terhadap Literasi Sains Peserta Didik (Meta Analisi) - Nurmaliati (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2025)
This study aims to analyze the impact (effect size) of the Problem Based Learning model on students' scientific literacy in science learning. The approach of this study is a meta-analysis involving 11 scientific papers from national and international publications. The meta-analysis study shows that there is a positive effect of using the Problem Based Learning model on students' scientific literacy, from 11 scientific papers analyzed, 4 articles have a high effect size category and 7 scientific papers have a medium effect size category. From the level of education (elementary, junior high and senior high school), the Problem Based Learning model has an average effect size with a high category. Meanwhile, from the subject matter, the Problem Based Learning model has a medium and high effect size category on the material or theme that can be analyzed through 11 scientific papers. From this meta-analysis, it can be concluded that the use of the Problem Based Learning model can increase the scientific literacy of students at elementary, junior high and senior high school levels.